1987
DOI: 10.1144/gsl.sp.1987.033.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry, Petrogenesis and Tectonic Environment of Circum-Superior Belt Basalts, Canada

Abstract: S U M M A RY: The Circum-Superior Belt of Proterozoic basalts and sedimentary rocks surrounds, and in some places, unconformably overlies the Archaean Superior Craton in northern Quebec, Canada. Four main groups of volcanic rocks are recognized. The oldest unit, the Eskimo Formation on the Belcher Islands, consists of subaerial massive continental tholeiites with 4-7% MgO, relatively high SiO 2 and K20, enriched LREE and other incompatible elements, negative Nb and Ta anomalies, and eNd (T = 1.8 Ga) of -7 to -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Pearce et al (1992) suggested the genesis of boninites by melting of depleted residual metasomatic MORB mantle where metasomatism is due to fluids and melts are derived from the dehydrated subducted slab. Earlier studies (e.g., Arndt et al 1987; reported the role of assimilationfractional crystallisation (AFC) of komatiites for the formation of boninites. The present dyke represents a Whundo type of magmatism and is not consistent with a komatiite AFC model in its genesis because of no record of komatiite in the vicinity.…”
Section: Discussionmentioning
confidence: 99%
“…Pearce et al (1992) suggested the genesis of boninites by melting of depleted residual metasomatic MORB mantle where metasomatism is due to fluids and melts are derived from the dehydrated subducted slab. Earlier studies (e.g., Arndt et al 1987; reported the role of assimilationfractional crystallisation (AFC) of komatiites for the formation of boninites. The present dyke represents a Whundo type of magmatism and is not consistent with a komatiite AFC model in its genesis because of no record of komatiite in the vicinity.…”
Section: Discussionmentioning
confidence: 99%
“…It may be (i) Archaean equivalent of modern boninites (Redman and Keys, 1985), (ii) volcanic equivalent of Late Archaean high-Mg norites (Sun et al, 1989;Hall and Hughes, 1990a), (iii) derived from a refractory mantle source (Sun and Nesbitt, 1978), and (iv) believed to be derived from komatiite through assimilation-fractional crystallisation (AFC) processes (Arndt et al, 1987;Sun et al, 1989). Here it is important to mention that high-Mg norites and some SHMB are not found to associate with komattite occurrences Hughes, 1987, 1990b).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is evident that this type of SHMB generally has spinifex texture similar to typical komatiites (Sun and Nesbitt, 1978;Zhou et al, 2002;Polat et al, 2006b), and is commonly intercalated with the coeval komatiite (Arndt et al, 1987;. For the Taishan SHMBs, notwithstanding that some late Archean komatiites occur in the TSGT, the following lines of evidence do not support the AFC model, plus crustal contamination, of the Taishan komatiites.…”
Section: Assimilation-fractional Crystallization (Afc)mentioning
confidence: 93%